AB0454 Suicidal ideation among patients with behcet's syndrome. (23rd January 2014) - Uzunaslan, D.; Saygin, C.; Hatemi, G.; Ozguler, Y.; Tascilar, K.; Yazici, H.; Hamuryudan, V.
Abstract : Background: An increased frequency of depression has been reported in Behcet's syndrome (BS) (1 ). While an increased suicidal ideation has been reported in other chronic rheumatologic conditions (2 ), this has been not studied in patients with BS. Objectives: To evaluate the frequency of suicidal ideation among BS patients and to delineate the factors predicting an increase in suicidal ideation. Methods: The frequency of suicidal ideation was evaluated with a standard questionnaire that was previously used (2 ), among BS patients with and without major organ involvement, ankylosing spondylitis (AS) patients who attended our outpatient clinic for their routine visits and a group of healthy controls. We questioned whether the subjects 1) thought that life was not worth living, 2) thought about ending their lives within the previous year, 3) ever planned to end their lives and if yes, whether they had planned to end their lives before the onset of their disease. In addition, Beck depression inventory (BDI) and Behcet's disease quality of life (BDQoL) questionnaires were filled. Disease activity was assessed using the Behcet's disease current activity form (BDCAF) for BS patients and BASDAI and BASFI for AS patients. Results: We surveyed 240 BS patients who had only mucocutaneous symptoms, 63 BS patients with active major organ involvement (30 eye, 31 vascular, 7 neurologic involvement), 50 patients with AS, and 106 healthy controls (Table ). Number of subjects who answered affirmatively to the second and third questions were significantly higher among BS patients with active major organ involvement compared to the other groups (p<0.001 and p=0.002). Among BS patients with active major organ involvement, 9/27 with eye, ¼ with neurologic, 3/27 with vascular, and 3/5 with more than one type of major involvement had thought of ending their lives. 9/27 with eye, 2/4 with neurologic, 3/27 with vascular and 2/5 with more than one type of major involvement had planned to end their lives. BS patients with eye involvement had the highest frequency of answering positively to these 2 questions (p<0.001 for each). None of the drugs that were used seemed to be associated with suicidal ideation. For each of the questions regarding suicidal ideation, the BDCAF, BDQoL and BDI scores of BS patients were higher among those who answered positively. Regardless of suicidal ideation, the BDI scores of BS patients with active major organ involvement were higher than AS patients and healthy controls. Conclusions: The frequency of suicidal ideation is increased among BS patients who have major organ involvement. This increase in suicidal ideation is correlated with higher disease activity and increased depression scores. Longitudinal studies are required for determining whether the frequency of suicidal ideation decreases with treatment and improvement in disease activity. References: Calikoglu E, et al. Dermatology.2001;203:238-40. Xie, et al. Rheumatol Int. 2012 Sep;32(9):2707-14 Disclosure of Interest: None Declared